TOXIC POSITIVITY PADA KORBAN YANG MENGALAMI BROKEN HOME: STUDI FENOMENOLOGI - Nasichatur Rohmah, Fitrotun; Rusyid Affandi, Ghozali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Toxic positivity is the tendency to maintain a positive mindset by suppressing negative emotions. This study aims to explore the phenomenon of toxic positivity among young adults in the context of individuals who have experienced a broken home, particularly those who practice it on themselves. This study employs a qualitative approach using a phenomenological method through in-depth interviews with two participants. The results indicate that toxic positivity emerges as an internal response to stress and problems, characterized by a tendency to suppress negative emotions, divert feelings, and force oneself to remain “fine” without deep emotional processing. The uniqueness of this study lies in its focus on individuals as perpetrators of self-directed toxic positivity.